การพัฒนาบทเรียนคอมพิวเตอร์ช่วยสอนที่เสริมสร้างทักษะการฟัง กลุ่มสาระการเรียนรู้ภาษาต่างประเทศ วิชาพม่าเพื่อการสื่อสาร สำหรับนักเรียนชั้นมัธยมศึกษาตอนต้น; THE DEVELOPMENT OF COMPUTER ASSISTED INSTRUCTION TO ENHANCE LISTENING SKILLS IN FOREIGN LANGUAGES LEARNING SUBSTANCE: MYANMAR SUBJECT FOR LANGUAGE AND COMMUNICATION FOR JUNIOR SECONDARY STUDENTS - (Siradol Sridadech), ศิรดล ศรีดาเดช; (Direk Teeraputon), ดิเรก ธีระภูธร; (Piyamanas Voravitrattanakul), ปิยมนัส วรวิทย์รัตนกุล (Journal of Education and Innovation, 2018)
งานวิจัยนี้นำเสนอการพัฒนาบทเรียนคอมพิวเตอร์ช่วยสอนที่เสริมสร้างทักษะการฟัง กลุ่มสาระการเรียนรู้ภาษาต่างประเทศ วิชา พม่าเพื่อการสื่อสาร สำหรับนักเรียนชั้นมัธยมศึกษาตอนต้น มีจุดมุ่งหมาย ดังนี้ 1) เพื่อสร้างและหาประสิทธิภาพของบทเรียนคอมพิวเตอร์ช่วยสอนที่เสริมสร้างทักษะการฟัง 2) เพื่อเปรียบเทียบทักษะการฟังก่อนเรียนและหลังเรียนของนักเรียนที่เรียนด้วยบทเรียนคอมพิวเตอร์ช่วยสอนที่เสริมสร้างทักษะการฟัง 3) เพื่อศึกษาความพึงพอใจของนักเรียนที่มีต่อการเรียนด้วยบทเรียนคอมพิวเตอร์ช่วยสอนที่เสริมสร้างทักษะการฟัง ของกลุ่มตัวอย่าง จำนวน 30 คน โดยการเลือกแบบเจาะจง เครื่องมือที่ใช้ในการวิจัย ได้แก่ บทเรียนคอมพิวเตอร์ช่วยสอนที่เสริมสร้างทักษะการฟัง แบบประเมินคุณภาพของบทเรียนคอมพิวเตอร์ช่วยสอนที่เสริมสร้างทักษะการฟัง แบบทดสอบวัดทักษะการฟังของนักเรียน และแบบวัดความพึงพอใจของนักเรียนที่มีต่อบทเรียนคอมพิวเตอร์ช่วยสอนที่เสริมสร้างทักษะการฟัง ผลการวิจัย พบว่า 1) ได้บทเรียนคอมพิวเตอร์ช่วยสอนที่เสริมสร้างทักษะการฟัง กลุ่มสาระการเรียนรู้ภาษาต่างประเทศ วิชาพม่าเพื่อการสื่อสาร สำหรับนักเรียนชั้นมัธยมศึกษาตอนต้น ประกอบด้วย 6 หน่วยการเรียนรู้ มีประสิทธิภาพเท่ากับ 82.21/83.06 2) ผลการเปรียบเทียบทักษะการฟังหลังเรียนสูงกว่าก่อนเรียน อย่างมีนัยสำคัญทางสถิติที่ระดับ .05 3) ความพึงพอใจของนักเรียนที่มีต่อบทเรียนบทเรียนคอมพิวเตอร์ช่วยสอนที่เสริมสร้างทักษะการฟัง อยู่ในระดับมาก ( = 4.41) THE DEVELOPMENT OF COMPUTER ASSISTED INSTRUCTION TO ENHANCE LISTENING SKILLS IN FOREIGN LANGUAGES LEARNING SUBSTANCE: MYANMAR SUBJECT FOR LANGUAGE AND COMMUNICATION FOR JUNIOR SECONDARY STUDENTS This research presents the development of computer assisted instruction to enhance listening skills in foreign languages learning substance: Myanmar subject for language and communication for junior secondary students. The purposes of this study were 1) to construct and find out the efficiency of the computer assisted instruction to enhance listening skills, 2) to compare the students’ pretest and posttest listening scores on the computer assisted instruction to enhance listening skills, and 3) to examine the satisfaction of students on the computer assisted instruction to enhance listening skills of the sample group consists of 30 students by using purposive sampling. The instruments used in this research were Computer assisted instruction to enhance listening skills, Quality assessment of computer assisted instruction to enhance listening skills, listening skills test and questionnaire of student satisfaction on computer assisted instruction to enhance listening skills. The result of study were as follows: 1) the computer assisted instruction to enhance listening skills consisted of 6 lessons and had the efficiency level at 82.21/83.06, 2) the results of listening skills, the students’ posttest scores were significantly higher than pretest scores at 0.5 level, and 3) the students’ satisfaction on the use of computer assisted instruction to enhance listening skills were at high level ( = 4.41).